Sudden increase of homicide in early 1970s Finland - Kivivuori, Janne (Journal of Scandinavian studies in criminology and crime prevention, 2002)
This paper describes the Finnish homicide trend between 1950 and 1999. The homicide rate decreased steadily and reached the lowest level of the century in the late 1960s. In the early 1970s, an abrupt increase in the homicide rate took place. The paper examines this rate shift by first disaggregating and then comparing the homicides of pre-increase years (1965-69) and increase years (1970-74). A database including all cases of interpersonal lethal violence between 1965 and 1974 is utilized. The analysis indicates increase of homicide reflected mainly male-to-male conflicts, the participants of which were increasingly often under the influence of alcohol. In a tentative interpretation, the homicide rate shift of the early 1970s is attributed to three factors: (1) a sudden liberalization of alcohol that the policy in 1969and the consequent increase of alcohol consumption, (2) weekend extension to Saturdays and (3) the coincidence in time of these political reforms with large scale social transformation and dislocation